Frequent problems and practical cases in securities - Saavedra Gil, Rony (2024)
The present investigation consists of analyzing, from the legal principles of securities, the frequent errors that originate at the time of issuance and subsequent collection of securities. Errors that we find when signing the security, when placing the DNI number in the security, regarding the amount of the security, when the security is altered, when the security is incomplete, such as exchange joint liability, encumbrances and effects on the security title, unclaimability, among others. That is, the obligation is certain, express, enforceable, liquid, illiquid and that the object of the provision is to give, do or not do. All of this, with the objective of detecting such errors in the issuance of securities in time, so that they obtain the corresponding exchange effects.